Proposal for Rural Credit and Training Program (RCTP): Phase II, 1983-1985 - BRAC (© BRAC, 2016)
1. Introduction 2. Proposal 3. Objectives 4. Credit operations 5. Training and technical services 6. Loan procedure 7. Expected outcomes